2017
DOI: 10.1161/hypertensionaha.117.09775
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum B-Cell Activating Factor Levels

Abstract: Hypertensive disorders of pregnancy are a leading cause of maternal and perinatal morbidity and mortality. Early suppression of B-cell lymphopoiesis is necessary for a normal pregnancy. Dysregulation of factors critical to B-cell survival may result in pregnancy complications, including hypertension. In this prospective observational study at a single medical center, serum levels of BAFF (B-cell activating factor) were measured in pregnant participants at each trimester, at delivery, and postpartum and in nonp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In this study, we investigated the role of specific cytokines, such as B-cell activating factor (BAFF), tumor necrosis factor α (TNF-α), and platelet-activating factor (PAF), together with some markers of oxidative stress, in pregnant women affected by GDM. It has already been observed that those signaling cytokines and inflammatory molecules have a role in the mechanisms of insulin resistance and may result in pregnancy complications such as maternal hypertension [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated the role of specific cytokines, such as B-cell activating factor (BAFF), tumor necrosis factor α (TNF-α), and platelet-activating factor (PAF), together with some markers of oxidative stress, in pregnant women affected by GDM. It has already been observed that those signaling cytokines and inflammatory molecules have a role in the mechanisms of insulin resistance and may result in pregnancy complications such as maternal hypertension [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…BAFF plays a role in determining insulin resistance [10][11][12] and has been implicated in GDM. BAFF is an essential immune regulator that was recently reported to be secreted by the placenta [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…As a proinflammatory cytokine, BAFF is elevated in patients with autoimmune or inflammatory diseases, such as inflammatory bowel disease, periodontitis, systemic sclerosis and so on [69]. Moreover, there is some research showing the expression of BAFF in reproductive tissues or female serum as well as addressing the importance of this cytokine in different reproductive diseases [10, 11]. During the early pregnancy, BAFF was rich in decidua and trophoblast.…”
Section: Introductionmentioning
confidence: 99%
“…These aspects of the experience have led some to conclude that birthing women inherently lack the competence to make decisions concerning their care. 106 The doctrine is further complicated by the presence of the fetus, especially in states where it is considered an independent legal entity. 107 Indeed, 'the fetus has become the dominant putative plaintiff in modern obstetric malpractice cases, distorting and diminishing the rights and remedies of birthing women as patients and as plaintiffs' .…”
Section: Legal Considerationsmentioning
confidence: 99%